9514 1404 393
Answer:
-2/5, -6
Explanation:
We assume you're asking for solutions to ...
(5x -(-2))(x +6) = 0
This can be simplified to ...
(5x +2)(x +6) = 0
__
The solutions are the values of x that make the factors zero. (The product can only be zero if a factor is zero.) Here, we'll find the zeros of the factors one at a time.
5x +2 = 0
5x = -2 . . . . . subtract the constant
x = -2/5 . . . . divide by the x-coefficient
__
x +6 = 0
x = -6 . . . . . .subtract the constant
The solutions of the equation are x = -2/5 or -6.
__
The graph shows the x-values that make the product zero.